“There Is a Silent War Going On”—African Religious Leaders’ Perspectives on Domestic Violence before and during the COVID-19 Pandemic - Frost, Marie-Luise (Religions, 2023)
The increase in domestic violence—particularly against women—is one of the most alarming indirect effects of the COVID-19 pandemic affecting countries worldwide. Following a mixed-methods approach, this paper examines religious leaders’ perspectives on and their engagement with this topic. It scrutinises the findings of the online survey Religious Leaders’ Perspectives on Corona, conducted from 2020 to 2021 by the Research Programme on Religious Communities and Sustainable Development at Humboldt-Universität zu Berlin. Most answers came from the African continent and showed that more female than male leaders perceived an increase in domestic violence during the pandemic or see the need to respond to this topic. However, both male and female participants warned that domestic violence is underreported, inter alia, because of religio-cultural norms. To illustrate how the relationship between women and men in marriage is understood and (re)interpreted and how domestic violence is addressed in individual communities, this paper additionally draws on semi-structured interviews with church leaders conducted in Burkina Faso, Ghana, Kenya, Nigeria, South Africa, Tanzania, and Uganda from 2017 to 2019 and in 2022. In addition to forms of support and advocacy against domestic violence, the examples also show that church leaders might call for women’s empowerment while upholding the idea of male headship.